Efektifitas Model Pembelajaran IDDEEE (Issue, Doing, Doing , Elaboration , Elaboration , Establish) Untuk Meningkatkan Kemampuan Berpikir Kreatif Pada Pembelajaran IPA di SMP - Anis Budi Rizkiyati; I Ketut Mahardika; Sudarti Sudarti (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2023)
In the era of the industrial revolution 4.0, we must have the ability to select, obtain, manage and follow information. Therefore, the ability to think critically, creatively, logically and systematically is required of us. But in reality, students' creative thinking skills in Indonesia, especially in science, are still relatively low. The purpose of this research is to examine the IDDEEE learning model to improve students' creative thinking skills. This type of research is development research using the 4-D development stages. The validity of the IDDEEE learning model was categorized as very valid. Based on the N-Gain value of creative thinking skills in small class test, large class test, and dissemination test, it can be concluded that the IDDEEE learning model can improve creative thinking skills in junior high school science learning.